The ageless stress between the individual and the collective: the case of corruption in Peru - Vivar-Mendoza, Aldo (2020)
Peru is a varied and convulsed country, and our republican history is a proof for that. The Peruvian health system has just been built during the 20th century. However, its development has been continuously affected by inadequate government policies and by corrosive and constant corruption acts. Now, in the 21st century, the health system has undergone some sort of reconstruction, but still with a very low budget and continuing venal practices that impede its proper functioning. This paper attempts to describe the anthropological basis underlying the human actions leading to corruption. It also reviews some of the main corruption modalities within the whole Peruvian healthcare system, a fragmented entity both in its public area and in its private counterpart. Also, some influencing factors are dealt with, as it is the case for the pharmaceutical industry. The resulting situation of the Peruvian healthcare system makes it quite vulnerable when facing sanitary crisis such as that generated by Covid-19. Finally, some proposals for change are outlined.